COLONIAL SLAVERY, CONTEMPORARY SLAVE LABOUR AND WORKERS’ HEALTH: A HISTORIOGRAPHICAL OVERVIEW (REVISTA DIREITOS, TRABALHO E POLÍTICA SOCIAL, 2021)
This paper problematizes the role of slavery in the history of the field related to workers’ health, providing a panoramic view on health, labour and slavery relations in the Americas as reported in academic literature. It addresses a conceptual debate on contemporary slave labour and workers’ health, presenting an schematic view of the health-labour-slavery studies describing three thematic axes – (a) health, labour and colonial slavery; (b) present day slavery legacy (c) impacts of contemporary slave labour on health. This process is aimed to highlight issues that deserve to be investigated in depth, as well as to stimulate a renewed research agenda and institutional actions in workers’ health beyond the challenges of combatting contemporary slavery.